Upaya guru bimbingan dan konseling untuk membina moral siswa - Rismayanti, Rismayanti; Hamonangan, Ronald Harries; Radyati, Ajeng (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the background of this research is the decline in student morals. The aim of the research is to determine the efforts made by guidance and counseling teachers to foster student morals. The research method used is a descriptive qualitative research method with interview, observation and documentation research instruments. The informants in this research were one guidance counselor and one student. The data analysis technique in this research is using the Miles and Huberman data analysis technique, activities in data analysis after data collection, including data reduction, data display, and data verification. After the author analyzed the data, the author was finally able to draw the conclusion that the guidance and counseling teacher's efforts to foster student morale at the Persada Husada Indonesia Vocational School, Bekasi City, were the BK Teacher implementing Guidance and Counseling Services, LDKS (Latihan dasar kepemimpinan siswa), Keputrian, dan Rokris (Rohani kristen).